2013
DOI: 10.1016/j.joca.2013.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Calcitonin delays the progress of early-stage mechanically induced osteoarthritis. In vivo, prospective study

Abstract: I.M. administration of Calcitonin seems to delay the progress of early-stage osteoarthritic lesions induced by mechanical instability in a rabbit experimental model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 51 publications
(42 reference statements)
1
12
0
Order By: Relevance
“…Further studies carried out in the canine Pond-Nuki model demonstrated that tiludronate exerts beneficial effects on gait disability and joint symptoms by improving some OA structural changes and reducing the synthesis of catabolic and inflammatory mediators [27]. Similar findings have been reported for calcitonin and estrogen use in different OA experimental models [16,[28][29][30][31][32][33][34][35][36][37][38][39][40]. Calcitonin prevented subchondral bone resorption and trabecular thinning associated to reduced cartilage degradation in a canine ACLT-induced OA model [28,29].…”
Section: Animal Studiessupporting
confidence: 65%
“…Further studies carried out in the canine Pond-Nuki model demonstrated that tiludronate exerts beneficial effects on gait disability and joint symptoms by improving some OA structural changes and reducing the synthesis of catabolic and inflammatory mediators [27]. Similar findings have been reported for calcitonin and estrogen use in different OA experimental models [16,[28][29][30][31][32][33][34][35][36][37][38][39][40]. Calcitonin prevented subchondral bone resorption and trabecular thinning associated to reduced cartilage degradation in a canine ACLT-induced OA model [28,29].…”
Section: Animal Studiessupporting
confidence: 65%
“…sCT administered intranasally reduced both subchondral bone remodelling and cartilage lesions in the early stages of OA 96 . Other studies reported beneficial effects following prophylactic and therapeutic intramuscular administration of sCT in cartilage lesions and bone turnover in the surgically induced OA rabbit model 97 . In a canine ACLT OA model 98 , subcutaneous injections of calcitonin under therapeutic conditions also reduced the progression of osteoarthritic cartilage and subchondral bone changes as well as the levels of serum markers of bone resorption.…”
Section: Calcitoninmentioning
confidence: 96%
“…A healed site was defined as a complete iso-opaque bridging bone callus connecting the two cortices (31). The osteo arthritis scale employed was modified from human and ca-nine osteoarthritis grading scales described previously in the literature (32)(33)(34). The scale used combined findings from the radiographs to describe the following grading scale: 0 = no evidence of joint effusion, osteophytosis, intra-articular mineralization or subchondral bone sclerosis; 1 = joint effusion present, loss or degeneration of articular cartilage; 2 = joint effusion and subchondral bone sclerosis present, minimal to mild osteophytosis; 3 = moderate to severe osteophytosis, intra-articular mineralization present or both; and 4 = appearance of subchondral cysts.…”
Section: Outcome Assessmentmentioning
confidence: 99%